Pioglitazone Attenuates Tactile Allodynia and Thermal Hyperalgesia in Mice Subjected to Peripheral Nerve Injury - Takehiko Maeda; Norikazu Kiguchi; Yuka Kobayashi; Masanobu Ozaki; Shiroh Kishioka (Journal of Pharmacological Sciences, 2008)
To clarify the role of peroxisome proliferator activated receptor γ (PPARγ) in neuropathic pain, we examined the effect of pioglitazone, a PPARγ agonist, on tactile allodynia and thermal hyperalgesia in a neuropathic pain model. Mice were subjected to partial sciatic nerve ligation (PSL) and given pioglitazone (1 – 25 mg/kg, p.o.) once daily. PPARγ was distributed in the neurons of the dorsal root ganglion and the dorsal horn of the spinal cord and in the adipocytes at the epineurium of the sciatic nerve in naive mice. PSL elicited tactile allodynia and thermal hyperalgesia for two weeks. Administration of pioglitazone for the first week after PSL attenuated thermal hyperalgesia and tactile allodynia, which was dose-dependent and blocked by GW9662 (2 mg/kg, i.p.), a PPARγ antagonist. Administration of pioglitazone for the second week also relieved tactile allodynia, but administration one week before PSL had no effect. A single administration of pioglitazone to mice on day 7 of PSL did not alter tactile allodynia and thermal hyperalgesia. PSL-induced upregulation of tumor necrosis factor-α and interleukin-6, which are essential for neuropathic pain, was suppressed by pioglitazone for the first week. This suggests that pioglitazone alleviates neuropathic pain through attenuation of proinflammatory cytokine upregulation by PPARγ stimulation. Keywords:: interleukin-6 (IL-6), neuropathic pain, partial sciatic nerve ligation, peroxisome proliferator activated receptor γ (PPARγ), tumor necrosis factor-α (TNF-α)